Pack-cyaniding: A Comparative Study of Low and High-Temperature Treatment - K. J. Akinluwade; A. L. Rominiyi; D. A. Isadare; A. R. Adetunji; M. O. Adeoye (Archives of Current Research International, 2018)
This study made a comparison between low and high-temperature pack cyaniding. Specific focus includes microstructure, surface hardness and case depth of treated samples. Standard specimens machined from mild steel were pack cyanided at 550°C (low temperature) and 950°C (high temperature) using processed cassava leaves with BaCO3 energizer and BaCl2 activator. The heat-treated samples were subjected to micro-examination with a LECO ASTM E384 Microhardness tester, Olympus BH-2 Advanced Optical Microscope and a Cam Scan Series 2 Scanning Electron Microscope. Results from these tests formed the basis for comparison.